Assume a financeRate of 1,000,000
The capitalCost = 1,000,000 + 5,000,000 which = 6,000,000
The financeRate then = 6,000,000 + 1,250,000 = circular.
Let's rearrange the formulas.
capitalCost = financeRate + estimateCost;
financeRate = capitalCost + tenantingCost;
Let's replace the financeRate in the first line with the definition of it from the second.
capitalCost = capitalCost + tenantingCost + estimateCost;
Subtract capitalCost from both sides
capitalCost - capitalCost = tenantingCost + estimateCost;
and we end up with this:
tenantingCost + estimateCost = 0.
So the original formulas are only valid when the tenantingCost and the estimateCost precisely cancel each other out - which has me too thinking that the formulas are wrong.
I see I repeated the same conclusion here as Jake. That'll learn me to keep a thread open for an hour or so before replying to it.